Pengaruh Kualitas Layanan, Kepercayaan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Marketplace Shopee - Shabara, Fidina Binta; Surianto, Moh. Agung (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
The Shopee marketplace often gets bad reviews from customers regarding the service provided, one of the reasons being the admin's lack of friendliness and delays in package delivery. The important objective of this research is to describe the impact of service, trust and customer satisfaction on customer loyalty in the e-commerce industry in Gresik Regency. The method used in this research is a quantitative method, this type of research is deductive research. The population in this research are Shopee marketplace users in Gresik Regency. This research requires a sample of 190 respondents using a purposive sampling technique with the criteria being the people of Gresik district who have made purchase transactions on the Shopee marketplace. The analysis method used is multiple linear analysis with the help of the SPSS application. The results of this research variables X1 and X3 both have a significant effect on variable Y, while variable X2 does not.